LIQUISOLID COMPACT TECHNIQUES: A REVIEW - Rokade, Manisha; Khandagale, Pradnya; Phadtare, Dipti (International Journal of Current Pharmaceutical Research, 2018)
The poor dissolution rate of water-insoluble drugs is still a substantial problem confronting the pharmaceutical industry. There are several methods used to increase the solubility of drugs, of those liquid-solid compact technique is a new and promising addition towards such a novel aim, that the solubility of the insoluble drug moiety is increased by the aid of non-volatile solvents and hence increasing the dissolution and bioavailability. Oral drug administration has been one of the most convenient and widely accepted routes of delivery for most of the therapeutic agents. It is one of the most extensively used routes of drug administration because of its obvious advantages of ease of administration, improved patient compliance, and convenience. The enhancement of oral bioavailability of poorly water-soluble drugs remains one of the most challenging aspects of drug development. A more recent technique, powdered solution technologyâ€ or Liquisolid technologyâ€, has been applied to prepare water-insoluble drugs into rapid-release solid dosage forms. The limited solubility of drugs is a challenging issue for the industry, during the development of the ideal solid dosage form unit. The technique is based upon the dissolving the insoluble drug in the nonvolatile solvent and admixture of drug loaded solutions with appropriate carrier and coating materials to convert into acceptably flowing and compressible powders.